Pemanfaatan Besi Scrap Sebagai Bahan Dasar Industri Peleburan Baja - Suyanto, Suyanto; Wibowo, Riyanto; Pramono, Sri (Universitas Ivet, 2021)
Many steel industries use scrap material as their basic material, both in the machine industry and the metal industry. The reason for using scrap is because this material is easy to obtain, has a high comparative value, has a chemical composition that is still very possible for further processing, and can reduce problems related to metal waste. Scrap material has a non-uniform type and chemical composition. The mistake in determining the type and composition of the basic ingredients will risk producing products whose specifications are not as expected. For that, before scrap is processed, it must first be grouped according to its type, then it is necessary to know in advance the chemical composition of each type of scrap ferrous material. Calculation of material composition before smelting must be precise, referring to the chemical composition standard that becomes the reference. The production of scrap iron into concrete reinforcing steel at PT Abadi Jaya Manunggal shows that scrap iron can be recycled and processed to produce reinforcing steel for concrete by taking into account the correct scrap composition. The chemical composition test results of scrap iron smelting show a composition identical to that of grade 250 steel. The result of the calculation of carbon equivalent is 0.317%, lower than the required maximum limit of 0.6%.